Wrought copper, Still and Brandy. Chile and Argentina, 1586-1854 (Quinto Sol, 2016)
The study examines the development of production, transport and distribution of copper carvings and stills to produce spirits in Chile and western Argentina, from the first recorded alembic (1586) until the mid-nineteenth century. It is detected that the main pole manufacturing of these devices was in the North of Chile, between Huasco and La Serena. From there, stills spread through a large space. The route of wrought copper and still spread over 5,000 kilometers, reaching the farms on both sides of the Andes, from Guayaquil (Ecuador), Callao (Perú) and Cinti (Bolivia) to the south frontier of the Spanish empire. Thus, an intense process of regional economic integration flourished, while the local agroindustry development with the possibility of distilled spirits strengthened. In this way, set the grounds for the emergence of several typical products.
Keywords: copper work; still; brandy; trans-Andean trade routes; typical products